Role of Teacher in the Classrom Management and Grouping Learners - Bakhriddinovna, Kipchakova Sanobar (Research Parks Publishing LLC, 2023)
This article describes the role of teacher in language teaching and effective classroom management, organizing the classroom and the learners. It discusses the ways of grouping learners or interaction patterns to use. The article also highlights tips about avoiding some classroom problems and possible reasons.